O espaço pátio no edifício escolar. Evolução e reinvenção - Sara Sofia Correia Gomes (2017)
The nature of the courtyard has trancended time and the programs that have been related to it. Although it was initially associated to the domestic use of the courtyard house, througout time, the courtyard has remained a structuring and aggregating element of the spaces that underlie it, managing to evolve with architecture and reinvent itself, satisfying the needs that the new themes generate and making its delimitation the reason why it is a place endowed with virtue, in a transversality of architectural programs. The use of the courtyard in study areas arose from the necessity to transpose the classroom and take the outside as essential for the quality of the teaching, but also for health reasons, contradicting the paradigm of school building and combining constructive processes with pedagogy, which allowed to ensure the relevance of outer space in the intelectual development and to integrate it as part of the spaces intended for teaching. Thus, the design of the school building began to accompany and reflect the growing complexity of the program content, transforming the courtyard into a place for socialization, but also for teaching. It is in the French lycées where the courtyard becomes an integral constituent of the organization and the development of the school space, and on which the first Portuguese lyceums were based on, but also the new typologies that have appeared later on. At the turn of the 21st century, the proliferation of several secondary schools in poor conditions and the need to transform the teaching plans led to the need to rethink the school space and rehabilitate it. Thereby, the courtyard appears as the structuring and aggregating elemento of the new solutions, affirming itself in the evolution and reinvention of the school space.